2017
DOI: 10.4103/1735-5362.202450
|View full text |Cite
|
Sign up to set email alerts
|

The effect of epicatechin on oxidative stress and mitochondrial damage induced by homocycteine using isolated rat hippocampus mitochondria

Abstract: Oxidative stress and mitochondrial dysfunction are the main suggested mechanisms for neurodegenerative diseases. In this study, we have evaluated the effects of epicatechin (EC) on mitochondrial damage induced by homocycteine (Hcy) using isolated rat hippocampus mitochondria in vivo. EC (50 mg/kg) was gavaged daily for a period of 10 days, starting 5 days prior to Hcy (0.5 μmol/μL) intra hippocampus injection in rats. Mitochondria were isolated from brain by different centrifuge techniques. Mitochondrial funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…We have reported in one study either cinnamon and green tea extract could have decreased blood sugar and induce weight gain individually and synergically in animal model of type-1 diabetes [6]. Also in another study we have shown anti-oxidative stress of epicatechin, a major component of green tea on oxidative stress and mitochondrial damage induced by homocycteine using isolated rat hippocampus mitochondria (Figures 1 & 2) [7]. Tea is an ordinary beverage in the world which have more than 4000 chemicals with different biological effects.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…We have reported in one study either cinnamon and green tea extract could have decreased blood sugar and induce weight gain individually and synergically in animal model of type-1 diabetes [6]. Also in another study we have shown anti-oxidative stress of epicatechin, a major component of green tea on oxidative stress and mitochondrial damage induced by homocycteine using isolated rat hippocampus mitochondria (Figures 1 & 2) [7]. Tea is an ordinary beverage in the world which have more than 4000 chemicals with different biological effects.…”
mentioning
confidence: 86%
“…Tea is an ordinary beverage in the world which have more than 4000 chemicals with different biological effects. Components of tea have anti-oxidant, antimutagenic and anti-carcinogenic effects [7,8]. Green tea has some protections against some neurological diseases such as Parkinson, Alzheimer and ischemic damages; it has also shown an anti-diabetic effect in insulin resistant animal models [7,9].…”
mentioning
confidence: 99%
See 3 more Smart Citations